Meningkatkan Motorik Halus Anak Melalui Kegiatan Mencetak di Toddler Rahmah El Yunusiyyah Padang Panjang: Improving Children's Fine Motor Skills through Printing Activities at Toddler Rahmah El Yunusiyyah Padang Panjang - Ita Rawiyah; lestari, Mega (Prodi Pendidikan Islam Anak Usia Dini Sekolah Tinggi Agama Islam Negeri Mandailing Natal- Sumatera Utara, 2021)
The fine motor skills of children in the Toddler Rahmah El-Yunusiyyah Padang Panjang group are still lacking, such as in using rigid writing instruments, children are not able to use pencils well, children still draw at one point. This research was conducted with the aim of improving children's fine motor skills through printing activities at Toddler Rahmah El-Yunusiyyah Padang Panjang. This type of research is Classroom Action Research (CAR) with the research subjects of students at Toddler Rahmah EL-Yunusiyyah Padang Panjang. The data in this study were processed using the percentage formula. The results of this study indicate that the improvement of children's fine motor skills through printing activities increases well. This can be seen from the success of the research cycle, where the first cycle gain was 33% at the first meeting, increasing to 39% at the second meeting, to 51% at the third meeting. In the second cycle, it increased to 62% at the first meeting, then increased to 76% at the second meeting and increased to 91% at the third meeting with an increase of 40%. Teacher activity in learning from cycle I to cycle II, which is 75% at meeting I, increased to 81% at meeting II and 84% at meeting III, in cycle two, increased to 87% at meeting I, increased to 90% at meeting meeting II, and increased to 96% at the third meeting in cycle II. From the increase in the cycle carried out, it can be concluded that this study succeeded in improving children's fine motor skills through printing activities.